2020
DOI: 10.15587/1729-4061.2020.203988
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the shape formation of hollow parts with a flange in the process of combined radial-reverse extrusion

Abstract: The simulation of the process of combined radial reverse extrusion of hollow parts with a flange has established two fundamentally different, in terms of the components of the kinematic modules, calculation schemes CDZ-1.i and CDZ-2.j, taking into conside ration the possible shape of the boundary of the section of a metal flow inside a workpiece. The comparison of the dependences of the optimal relative rate of metal outflow in the opposite direction for different schemes indicates significant differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…The development of capabilities of the energy method of power balance based on the expansion of the base of kinematic modules of complex configuration was addressed in a series of works [29][30][31][32][33][34][35][36]. Papers [29,30] suggested techniques for simplifying the power of plastic deformation forces using a minimizing function in a general form.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of capabilities of the energy method of power balance based on the expansion of the base of kinematic modules of complex configuration was addressed in a series of works [29][30][31][32][33][34][35][36]. Papers [29,30] suggested techniques for simplifying the power of plastic deformation forces using a minimizing function in a general form.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…That allowed the authors, among other things, to acquire data on the shape change in a semi-finished article within the ratios of the deformation process chosen for the cited study. The main research results reported in [32,35] make it possible to take into consideration the peculiarities of tool configuration, the shape of the boundaries of the distribution of a metal flow inside the workpiece. The authors identified the complication of the mathematical apparatus when deriving the value of the reduced deformation pressure (in an analytical form) inside the kinematic module of a triangular or trapezoidal shape with slanting boundaries.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…This makes it possible to evaluate the expansion of the technological capabilities of this deformation process. The possibilities of the energy method for obtaining analytical dependencies of the force mode of deformation and features of forming in the processes of combined radial-reverse extrusion are demonstrated in the works [5,15,19,20]. These studies used the kinematic element method to calculate the value of the reduced strain pressure as the total value for the components of unified modules of rectangular, triangular and trapezoidal shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Beam-signal and other devices of active action of the IR range have significant operational advantages at the working lengths of the EMW, which correspond to the "windows" of the transparency of the atmosphere in the middle range of the IR spectrum: (3.3 -4.2) μm, (4.5 -5. 1) μm, (8)(9)(10)(11)(12)(13) μm. Modern technological advances in the production of ultra-bright p-n-emitters in these parts of the spectrum require further study of the mechanisms of formation of the basic physical and technical characteristics of multicomponent beam-diode sources of directional action.…”
Section: Introductionmentioning
confidence: 99%
“…A simplified parametric model is selected for the empirically obtained data set. Such analytical models are the basis for the classification of the main types of LIC for sources of any radiation mechanism [7,8,9]. Together with the idealized diagram f(θ)=cos -3 •θ (θ -a polar distance) there are 8 such types.…”
Section: Introductionmentioning
confidence: 99%